AD, Volume 17, n° 1, 1992 - Full Issue - Journal System (Africa Development, 1992)
Table of Contents Collective Rights, Transformation and Democracy Some Thoughts on a New Constitutional Dispensation in South Africa Jennifer Clare Mohamed ................. 5 Traditions de l'autoritarisme et problèmes de gouvernement en Afrique sub-saharienne Achille Mbembe ............................. 37 The African Informal Sector at the Crossroads: Emerging Policy Options Crispin Grey-Johnson .......................... 65 Restructuration et Evolution de l'Emploi dans le Secteur Public et Para-Public en Cóte-ďlvoire Kouadio Benie Marcel ......................... 93 Multilingualism and Problems of Choice of Indigenous Official Languages in the West African Sub-Region A. E. Sosu ..................................... 113 Book Reviews The Development of African Capitalism Tiyambe Zeleza ............................... 129 Sam ir Amin and the New International Epistemological Order Timo Lyyra .................................. 137 Index of Africa Development Vol.XVI, 1991 ..................... 147